Of the people, for the people, by the people : a case study of Friends of Orchha - Chowdhary, Nimit, (SAGE Business Cases., 2013)
The case is about a rural homestay start up that endeavours to promote responsible and sustainable source of livelihood for families below poverty line who are desperately in need of work. The idea is to intertwine income generation with empowerment, development, vocational and health care micro sub projects to create a model hamlet based on Employee Ownership Share Plan (EOSP). The case centres on the challenges that emerge for the start-up in terms of succession planning and professional management.